The Influence of Librarians’ Innovation on the Fulfillment of Local Information Needs at the Library and Archives Office of Pariaman City - Meka Arisma Sari; Marlini (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Rapid technological advancement and rising user expectations have increased the need for librarians to develop innovative and adaptive services, particularly in meeting communities’ local information needs. This study aims to examine the influence of librarians’ innovation on the fulfillment of local information needs at the Library and Archives Office of Pariaman City. A quantitative approach with a descriptive-associative design was employed. The study involved a population of 1,516 library users, from whom 94 respondents were selected through purposive sampling. Data were collected using a structured questionnaire and analyzed through descriptive statistics, Pearson correlation, and simple linear regression. The findings indicate that librarians’ innovation was perceived at a high level (mean = 3.08), while the fulfillment of local information needs was likewise categorized as high (mean = 3.16). Librarians’ innovation had a positive and significant relationship with the fulfillment of local information needs (r = .481, p < .001) and explained 23.1% of the variance in this outcome. The study concludes that librarians’ innovation plays an important role in strengthening local information services. These findings contribute to public library service research by demonstrating the relevance of librarians’ innovative practices to local information provision and imply that public libraries should strengthen librarians’ competencies, promote continuous service innovation, and optimize local information management to improve service quality and sustainability.